Bioaccumulation of poly-aromatic hydrocarbons in plankton, algae and fish in south sea waters in Jogjakarta - Lukitaningsih, Endang (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
As a pollutant, the presence of Poly Aromatic Hydrocarbons (PAH) in the environment must be always monitored, because of their ability to spread widely through the food chain and also their carsinogenic properties. The solubility of PAH in water is very low, therefore it is difficult to analyze their presence in water environment by using water as a sample. By utilizing the phenomenon of the accumulation of PAH in biolipids, the analysis method has been developed using bioindicators. In this research, the concentration of four kinds of PAH (pyrene, benzo(a)anthracene, benzo(k)fluoranthene and perylene) in several samples (water, plankton, algae and fish) that collected from the south sea Jogjakarta has been determined. The bioaccumulation factor (BAF) of PAH in each sample has been calculated and the results were from 4498 to 432754; 2552 to 49265; 14156 to 730991, respectively for plankton, algae and fish. Based on the BAF values, plankton can be used as a bioindicator for short term PAH monitoring, while the Upeneus moluccensis fish primarily gills organ can be used as a bioindicator for medium term (months) PAH monitoring.Key words : poly aromatic hydrocarbons, bioaccumulation factor, bioindicator, Upeneus moluccensis